Road counts reveal The Gambia's West Coast region still has the densest population of Hooded Vultures Necrosyrtes monachus in Africa. (16th December 2022) - Jallow, Mawdo; Dibba, Momodou L; Camara, Fagimba; Barber, David R; Bildstein, Keith L; Thompson, Lindy J
Abstract : Road surveys are a useful tool for comparing vulture population trends. Here we present data from road surveys to count Hooded Vultures Necrosyrtes monachus in The Gambia in 2017 and 2021. In the first nationwide road survey in November 2017 (during this species' breeding period), we counted 7.3 Hooded Vultures per km. In The Gambia's West Coast, we counted 33.3 Hooded Vultures per km in November 2017 (during this species' breeding period) and 27.4 Hooded Vultures per km in May 2021 (during the non-breeding period). In the rest of the country (i.e. in The Gambia's North Bank, Central, Upper and Lower River regions), we counted 3.3 Hooded Vultures per km in November 2017 and 2.1 Hooded Vultures per km in November 2021, which may represent cause for concern. These figures for The Gambia's West Coast region far exceed the results of road surveys conducted in the same area in 2005, 2013, and 2015. The number of Hooded Vultures recorded per km in the West Coast region increased from 2005 to 2017, but dipped slightly into May 2021, when we would have expected to see an increase, as the 2021 survey was carried out in the non-breeding period. In the non-breeding period vultures would not be confined to nests and populations should be at their highest, due to recently fledged juveniles entering the population. Overall, the densities of Hooded Vultures counted in The Gambia from 2005 to 2021 indicate that population densities are higher in The Gambia than in any other country where road surveys have taken place. The densities were orders of magnitude higher than those in eastern and southern Africa. However, given the decline in numbers between 2017 and 2021, we should not be complacent about the stability of this population.